2021
DOI: 10.1007/s10508-021-02005-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Functional, and Metabolic Brain Differences as a Function of Gender Identity or Sexual Orientation: A Systematic Review of the Human Neuroimaging Literature

Abstract: This review systematically explored structural, functional, and metabolic features of the cisgender brain compared with the transgender brain before hormonal treatment and the heterosexual brain compared to the homosexual brain from the analysis of the neuroimaging literature up to 2018, and identified and discussed subsequent studies published up to March 2021. Our main aim was to help identifying neuroradiological brain features that have been related to human sexuality to contribute to the understanding of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 114 publications
0
11
0
Order By: Relevance
“…Second, the menstrual cycle of cis women and trans men was not accounted as a variable of interest, while there is growing evidence of functional dynamic differences between the phases of the menstrual cycle (De Filippi et al, 2021 ). Likewise, the sexual orientation of all participants was not systematically assessed as a variable of interest (Frigerio et al, 2021 ; Guillamon et al, 2016 ; Skorska et al, 2021 ). Including minority gender groups when investigating the gender phenomenon in the brain is imperative to understand the complexity of the gender experience.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the menstrual cycle of cis women and trans men was not accounted as a variable of interest, while there is growing evidence of functional dynamic differences between the phases of the menstrual cycle (De Filippi et al, 2021 ). Likewise, the sexual orientation of all participants was not systematically assessed as a variable of interest (Frigerio et al, 2021 ; Guillamon et al, 2016 ; Skorska et al, 2021 ). Including minority gender groups when investigating the gender phenomenon in the brain is imperative to understand the complexity of the gender experience.…”
Section: Discussionmentioning
confidence: 99%
“…A second theoretical perspective is the neurohormonal hypothesis, which posits that prenatal androgen exposure organizes parts of the brain (in terms of structure (23) and function (24)) as well as sex-differentiated psychological and behavioral characteristics (25), including gender identity and sexual orientation. The surge in sex hormones during adolescence is argued to influence parts of the brain to be further expressed in a relatively male-or female-typical manner, based on the earlier prenatal brain organization (6)(7)(8)(9)(26)(27)(28). On average, sex differences in functional connectivity that are consistent with the neurohormonal hypothesis have been reported (e.g., 13,[29][30][31][32], although there are ongoing debates regarding the extent of sex differences in various brain features, including functional connectivity (e.g., [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…According to a growing body of research, prenatal factors impacts on sexual gender orientation, neuroanatomical and other biological connections have been discovered [13]. Multiple studies conducted have shown differences between structures and activities of the brain in homosexuality compared to heterosexuality [14][15][16]. Sexual minority adolescents are also more vulnerable to child abuse [17], peer bullying [18], and other types of violence than their heterosexual counterparts, which further contribute to the manifestation of mental disorder like schizophrenia [19].…”
Section: Introductionmentioning
confidence: 99%